Lost and Found-Unfolding and Refolding Aesthetic Learning Processes - Annika Hellman; Ulla Lind (MDPI AG, 2021)
The ongoing marketisation of education is a great loss for visual arts education since explorative learning processes are marginalised in favour of more goal-oriented learning. The empirical material analysed in this research derives from the visual art portfolio of a student from an elective university course in visual arts education. Working within Deleuze and Guattari's philosophical framework, we examine the folding, unfolding, and refolding of aesthetic learning processes, suggesting productive concepts and practices. The analysis made us aware of our own pedagogical ideals and the loss of having to disassemble them, in line with the new curricula. The student's visual learning process showed us how to reassemble new and explorative learning processes, assigning aspects of sustainability and an ethics of care in relation to environmental and social questions. We suggest strategies for learning in the folds, where educators are called upon to prepare students for an uncertain future. This demands a creative imagination, an ethical standpoint for negotiating the curriculum in line with differentiation by forming, inventing, and fabricating new concepts and images.